Epigenetic profiles in polyglutamine disorders. (January 2018) - Liu, Hongmei; Tang, Tie-Shan; Guo, Caixia
The dominant polyglutamine (polyQ) disorders are a group of progressive and incurable neurodegenerative disorders, which are caused by unstable expanded CAG trinucleotide repeats in the coding regions of their respective causative genes. The most prevalent polyQ disorders worldwide are Huntington's disease and spinocerebellar ataxia type 3. Epigenetic mechanisms, such as DNA methylation, histone modifications and chromatin remodeling and noncoding RNA regulation, regulate gene expression or genome function. Epigenetic dysregulation has been suggested to play a pivotal role in the pathogenesis of polyQ disorders. Here, we summarize the current knowledge of epigenetic changes present in several representative polyQ disorders and discuss the potentiality of miRNAs as therapeutic targets for the clinic therapy of these disorders.